The British Naval Boarding Axe. (3rd July 2019) - Lee, David
Abstract : This article presents the current state of knowledge of British boarding axes. It examines the two models of boarding axe used by the Royal Navy as well as British made axes privately purchased for use in merchant ships. It gives an overview of their use, identifies the main types and records the known manufacturers. It also uncovers an axe that may have been used by the Royal Navy in between the two types already recognized.